Synthesis and Characterization of Two Novel Bidentate N,O-Coordinated Schiff-base Compounds - Sheikhshoaie, Iran; Hosein Mashhadizadeh, Mohammad (Asian Journal of Chemistry, 2016)
Two new mono azo Schiff-base ligands 5-[((4-methyl phenyl) azo)-N-(2-aminopyridine) salicylaldimine] (S1) and 5-[((4-methyl phenyl) azo)-N-(2-amino-1,2-dicyanomalonitrile) salicylaldimine] (S2), were reported by the reaction of suitable precursor ligands with 2,6-diaminopyridine and 1,2-diamino dicyano ethylene. Elemental analysis, 1H-NMR, 13C-NMR, UV, FT-IR and G.C. mass spectroscopy methods characterized the prepared compounds. Some theoretical calculations on the nonlinear optical properties of these Schiff base ligands by AM1 semiempirical method (Austin Model 1) have also been investigated.